2005
DOI: 10.1158/0008-5472.can-04-4262
|View full text |Cite
|
Sign up to set email alerts
|

RedirectingIn vivoElicited Tumor Infiltrating Macrophages and Dendritic Cells towards Tumor Rejection

Abstract: A hostile tumor microenvironment interferes with the development and function of the adaptive immune response. Here we report the mechanisms by which large numbers of tumor-infiltrating macrophages and dendritic cells (DC) can be redirected to become potent effectors and activators of the innate and adaptive immunity, respectively. We use adenoviral delivery of the CCL16 chemokine to promote accumulation of macrophages and DC at the site of preestablished tumor nodules, combined with the Toll-like receptor 9 l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
373
0
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 510 publications
(406 citation statements)
references
References 39 publications
16
373
0
9
Order By: Relevance
“…Based on the M1 versus M2 paradigm of macrophage polarization [6], inhibition of M2-and activation of M1-inducing signals (e.g. IL-10 and CpG, respectively) was proposed as a possible strategy to restore the anti-tumor functions of TAM [7,8]. Recent investigations suggest that during tumor growth both innate and adaptive immune cells participate in guiding the pro-tumoral phenotype of TAM [9].…”
mentioning
confidence: 99%
“…Based on the M1 versus M2 paradigm of macrophage polarization [6], inhibition of M2-and activation of M1-inducing signals (e.g. IL-10 and CpG, respectively) was proposed as a possible strategy to restore the anti-tumor functions of TAM [7,8]. Recent investigations suggest that during tumor growth both innate and adaptive immune cells participate in guiding the pro-tumoral phenotype of TAM [9].…”
mentioning
confidence: 99%
“…Tumor-associated macrophages constitutively express IL-10 [34], thus maintaining an impaired immune status. We and others [35,36] have reported that IL-10 receptor blockade, when combined with TLR agonists and/or other immunostimulatory agents, rescue the functional paralysis of tumor-infiltrating DCs and macrophages toward an efficient cancer therapy. However, macrophages are not the sole IL-10 source in tumors.…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, in a murine tumor model, others have shown that CD25 1 -cell depletion and IL-10 receptor blockade exert distinct, though partially overlapping, effects in suppressing DC activation and anti-tumor CD8 1 response [13]. Even if a Foxp3-directed, rather than CD25-directed, Treg-cell depletion may provide more reliable results about the functional redundancy of Treg cells and IL-10, it is likely that Treg cells are not the only source of IL-10 at the tumor site [13] and that sole IL-10 receptor blockade cannot recapitulate the efficient anti-tumor activity of combination therapies [35,36], of the sole OX40 triggering [3,21] or of Foxp3-targeted Treg-cell depletion, when combined to vaccination [39] or even as single treatment [40].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, TIDC in non-glioma tumors have been described as playing several roles in the anti-tumor response. In hepatocarcinoma and colon carcinoma, functional impairment of TIDC can be reversed by IL-10 neutralization combined with CpG stimulation [34,35]. In contrast, melanoma-derived TIDC are potent APC and can mediate tumor rejection without prior re-stimulation [36].…”
Section: Discussionmentioning
confidence: 99%